Rosa Barba : time as perspective - Øvstebø, Solveig; Varadinis, Mirjam; Bergen kunsthall; Kunsthaus Zürich (Ostfildern : Hatje Cantz, 2013)
"Rosa Barba works with the basic elements of the cinema: celluloid, light, projector, and sound. She dissects the structure of the narrative and plays with the often improbable characters, places, and stories of the medium of film. Her exploration of space, time, and language is crucial to the process. This publication presents her new project, which, like a story or a play in different acts, stretches out across two exhibition chapters. The project revolves around a 35mm film, Time as Perspective, which Barba shot during the spring in Texas--fascinated by the desert landscape, which she approaches from an almost archaeological perspective on a quest for inscribed signs and times." --Publisher description.
Newspaper : time as perspective : June 6-September 9, 2012, Kunsthaus Zürich -- Sun Clock -- Subconscious society -- A story about a story / Laurie Anderson -- A home for a unique individual -- What an editing room is / Harun Farocki -- Lecture drawings on perspective / J.M.W. Turner -- Singetraum / Ingrid Wiener -- THe concept of geological time / Giovanni P. Ricciardi -- White museum, 2011 -- Backdoor exposure -- Time as perspective : February 2-March 17, 2013, Bergen Kunsthall.
Contributions by Laurie Anderson, Harun Farocki, Giovanni P. Ricciardi, Ingrid Wiener.
Published on the occasion of an exhibition held at Kunsthaus Zürich, Zürich, June 6 - September 9, 2012; Bergen Kunsthall, Bergen, February 2 - March 17, 2013.
boek
Keywords: Barba, Rosa, -- 1972- -- Exhibitions